Application of coal-powder borehole-sealing material in borehole-sealing engineering. Issue 2 (3rd May 2019) - Li, Hui; Guo, Shaoshuai; Chen, Haidong
Abstract : In order to make scientific analysis of the material of the coal-powder borehole-sealing technology and verify its actual sealing performance, the authors performed studies involving laboratory experiments and field tests. The research results are shown as follows. ( a ) The borehole-sealing material has good microexpansion properties. With an increase in additive proportion, the expansion and strength of the sealing material increase. In addition, contraction expansibility is also affected by the water/material ratio of the slurry. The smaller the water/material ratio is, the greater the degree of deformation becomes. ( b ) Considering the coal-powder borehole-sealing material's expansion properties, strength characteristics and application cost determined the optimum composition ratio of the coal-powder borehole-sealing material: the volume of coal powder accounted for 70% and the additive volume accounted for 30%. In this condition, the expansion rate and maximum compressive strength of the sealing material are 6‰ and 7·30 MPa, respectively. ( c ) The gas concentration extracted out of the borehole sealed by using the coal-powder sealant is slightly higher than that for the borehole sealed by using expansive cement (72·50 and 69·65%, respectively).